EVALUATION OF CONSUMER BEHAVIOR IN ELECTRONIC PRODUCT ADOPTION: CASE STUDY IN FINANCE XYZ - Novi Yanti; Dina Adawiyah; Sunreni , Sunreni (Journal of Social and Economics Research, 2023)
The aim of this research is to determine the extent of influence of consumer behavior, including cultural factors, social factors, personal factors and psychological factors, on purchasing decisions for electronic products at Finance XYZ in Padang City with a sample size of 30 people. Data was obtained through distributing questionnaires. Research data processing was carried out using respondent data analysis and assisted by SPSS. Testing of statements is carried out through validity and reliability tests, as well as classical assumption testing which includes normality, linearity and heteroscedasticity tests. The results of multiple linear regression analysis tests show that each variable used in this research has a regression coefficient which can be represented by the following multiple regression equation: Y = 0.063 + 0.218X1 + 0.035X2 + 0.201X3 + 0.917X4. Thus, it can be concluded that cultural factors and social factors have a positive influence on the decision to purchase gold installment products, personal factors and psychological factors have a positive and significant influence on consumers' decisions to purchase electronic products from Finance XYZ